Police discrimination and police distrust among ethnic minority adolescents in Germany - Kogan, Irena; Weißmann, Markus; Dollmann, Jörg (Frontiers in Sociology, 2024)
In light of ongoing debates about racially motivated police violence, this paper examines two separate but interrelated phenomena: instances of police discrimination and mistrust in police and the judicial system among ethnic minorities in Germany. Analyses are carried out based on waves 1, 3, and 5 of the CILS4EU-DE data collected among 14 to 20 year-old respondents in Germany. The focus of the paper lies on young men from the Middle East, as well as Northern and Sub-Saharan Africa, who—as our study demonstrates—tend to disproportionally more often report discrimination experiences and particularly low levels of trust in police and courts compared to other ethnic minorities and the majority populations in Germany, and partially also in comparison to their female counterparts. We also show that more frequent experiences of police discrimination are associated with greater distrust of the police and partially also with courts among young men from the Middle East, North and Sub-Saharan Africa. Female adolescents from similar backgrounds are also more distrustful of the police, but this is not explained by their own experiences of police discrimination.